Health and equity impacts of a large oil project in Africa - Jobin William (The World Health Organization, 2003)
A system of external reviewers was established by the World Bank Group to promote a thorough environmental and health impact assessment for the US$ 3.5 billion Chad Oil Export Project, based on a loan request from Chad, Cameroon and a consortium of oil companies. The environmental and health assessment process showed evidence of its ability to minimize the number of deaths from malaria, traffic accidents and construction accidents and the occurrence of minor sexually transmitted diseases, diarrhoeal diseases and respiratory diseases; it also probably limited adverse impacts on wildlife and tropical ecology along the pipeline route. However, the system was unable to deal with the larger issues, which included: the intrinsic unsustainability of this kind of extraction project; its eventual contribution to large amounts of greenhouse gases in the atmosphere; the lack of equity in sharing the risks, negative impacts, benefits and decision-making among the various participants in the project; and the possible acceleration of transmission of the AIDS virus into central Africa. Unfortunately, the international panel of experts appointed by the World Bank Group was largely ignored by the project proponents, and had little success in minimizing the most serious impacts or in improving the social equity of the project.